Services policy reform in the People's Republic of China: Before and after the global financial crisis - Ying Fan (Asian Development Bank Institute (ADBI), 2011)
Adverse effects of the global financial crisis on international trade include falling demand, increased trade protectionism, and drying up of trade finance. Much attention has focused on the impact of the crisis on goods trade; however literature on its impact on services trade is limited, especially on the services trade in the People's Republic of China (PRC). This paper analyzes the impact of the global financial crisis on the PRC's services trade, discusses policy responses by the government, and puts forward policy suggestions. The main findings of the paper are as follows: Although the global economic and financial crisis spawned a synchronized recession leading to a contraction in the PRC's services trade, the crisis has had a moderate effect on the PRC's trade in services because of the lower internationalization of services. The PRC's trade surplus in goods decreased and its trade deficit in services increased after the crisis. Structural reforms are now urgently needed to help support the recovery of output and trade. A possible solution to rebalancing the trade balance (trade surplus in goods and trade deficit in services) would be to expand trade in services. The degree of openness for services is lower than for goods in the PRC. Further liberalization in services trade is the appropriate policy choice for the government. Continued policy and regulatory reform in favor of services trade will be vital to supporting economic recovery. Improved market access and national treatment of foreign service suppliers would help enhance the productivity and competitiveness of local services firms and upgrade the industry structure of services, which is essential for the country's economy to change from being driven by exports to being driven by domestic demand. Decreasing trade and investment barriers would help expand services trade and investment, and increase PRC involvement in the globalization of services.
Keywords: F13; F14; 330; Finanzmarktkrise; Internationaler Dienstleistungsverkehr; Außenhandelseffekt; Außenwirtschaftspolitik; China